EFFECTIVENESS OF NUTRITIONAL INTELLIGENCE PROGRAM TOWARDS IMPROVING MATERNAL KNOWLEDGE AS AN EFFORT TO PREVENT STUNTING IN CHILDREN - Aulia Irhamna Irhamna; Alifah Indalika Mulyadi Razak (SEA-CECCEP, 2021)
Nutrition is an important source of energy for children to be able to absorb learning information. Various studies have shown that good eating habits, nutritional balance of composition, and physical activity can support children's development. In line with the results of the study, there needs to be a sustainable learning pattern so that the child can easily understand about nutrition, namely parents as the nearest environment of the child as an effort to prevent stunting cases in the child. The participants of this study were 30 mothers in Bojongsoang District, Bandung Regency, West Java Province.  This research aims to test the effectiveness of nutritional intelligence programs in mothers as stunting efforts in children through the design of the-before-after study design experiment with two experimental and control research groups. Specifically packaged in the form of training activities that include materials: (1) cooking; (2) healthy eating; (3) fitness; and (4) fun. In general, the average maternal knowledge score of nutritional intelligence and stunting in the experiment group (Mpre test = 97.5 and Mpost test =123.7) both pre-test and post-test had higher scores than the control group (Mpre test = 97.3 and Mpost test= 88.5). By comparison, the control group's pre-test and post-test scores decreased by 4.7%, while the experiment group saw an 11.8% increase in scores. The effectiveness of the learning model can be measured through Mann Whitney tests that compare the average pre and post test scores measured through stunting instruments, which are demonstrated through the significance of scores in the control group and experiments after being given nutritional intelligence programs. This means that nutritional intelligence programs are considered effective in increasing maternal knowledge as an effort to prevent stunting in children.